Pembangunan Repeater Radio di Daerah Terpencil untuk Koordinasi Sistem Tenaga Listrik - Suhardhika Sih Sudewanto (Sekolah Tinggi Teknik PLN, 2020)
Expansion of the electrical network and substation makes a demand for better electricity system coordination. A radio communication system is one of many ways that fulfill such demand. The range of radio communication systems is limited by geographical location. Establishing a series of radio links to cover a wide area can not be considered as a solution to have good quality and reliable radio communication system anymore. Therefore, It needs one optimal location for radio repeater to cover all sites that have a crucial role in electricity system coordination. The optimal location for the mountainous geographical region is usually located in a remote area, far from civilization. It will need more effort on engineering to establish a radio repeater site. The selection method of location and development phase will be done by software simulation and actual survey to conduct testing, to determine the equipment needed to build radio repeater, and for administrative purposes. With the average fade margin of 25 dB, the location of the radio repeater is considered optimal enough to maximize electricity system coordination.